Expanding Health Insurance for the Elderly of the Philippines - Michael R.M. Abrigo; Timothy J. Halliday; Teresa Molina (Institute of Labor Economics (IZA), 2019)
This paper evaluates a Filipino policy that expanded health insurance coverage of its senior citizens, aged 60 and older, in 2014. Using regression discontinuity and difference-in-differences methods, we find that the expansion increases insurance coverage by approximately 16 percentage points. We show that the compliers, those induced by the policy to obtain insurance, are disproportionately female and largely from the middle of the socioeconomic distribution. Instrumental variables estimates indicate that out-of-pocket medical expenditures more than double among the compliers. We argue that this is most likely driven by an outward shift in the medical demand curve.
Keywords: I10; I13; I14; 330; insurance; medical demand; compliers; Philippines